Can population projections be used for sensitivity tests on policy models? - John Bryant (New Zealand Government, The Treasury, 2003)
Many policy models require assumptions about future population trends. Sensitivity tests for these assumptions are normally carried out by comparing population projection variants. This paper outlines some of the conditions that variant-based sensitivity tests must meet if they are to be informative. It then describes four common situations where these conditions are not met, so that conventional sensitivity tests are not informative. The solution, the paper argues, is stochastic population projections.
Keywords: C52; E17; J11; 330; Demography; Sensitivity testing; Population projections; Policy modelling